Fe Overload and Ascorbyl Radical Steady State Concentration in Rat Brain - Piloni, Natacha E.; Puntarulo, Susana (Issues and Developments in Medicine and Medical Research Vol. 4, 2022)
The one-electron oxidation of ascorbate produces the ascorbyl radical , that has been proposed as a marker of oxidative stress either in vitro, or in vivo in numerous systems. The application of a simple kinetic analysis allowed us to estimate the steady state concentration of . These data were successfully compared to experimental values obtained in rat brain under physiological conditions and in response to stress due to sub-chronic Fe overload. The main objective of this chapter is to further explore the information presented in a previously published manuscript employing a simple kinetic model developed to estimate steady state concentration to other Fe-dependent oxidative conditions in rat brain. This analysis shows that acute Fe-overload, seems to affect steady state concentration by a more complex pathway network than sub-chronic Fe-overload. The mechanistic study presented here will help to understand the mechanisms that govern the responses of living organisms to toxicologically relevant challenges.